2018
DOI: 10.1017/s2040174418000430
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal exposures to phthalates and phthalate mixtures result in sex-specific effects on body weight, organ weights and intracisternal A-particle (IAP) DNA methylation in weanling mice

Abstract: Developmental exposure to phthalates has been implicated as a risk for obesity; however, epidemiological studies have yielded conflicting results and mechanisms are poorly understood. An additional layer of complexity in epidemiological studies is that humans are exposed to mixtures of many different phthalates. Here, we utilize an established mouse model of perinatal exposure to investigate the effects of three phthalates, diethylhexyl phthalate (DEHP), diisononyl phthalate (DINP) and dibutyl phthalate (DBP),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 63 publications
1
25
1
Order By: Relevance
“… 38 , 39 The 5 mg/kg-day dose used in this study falls within or below the range of no-observed-adverse-effect level (NOAELs) for oral DEHP exposure established by US and European agencies 4 , 40 and is estimated to result in an amniotic fluid concentration within the ranges observed in human amniotic fluid. 6 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“… 38 , 39 The 5 mg/kg-day dose used in this study falls within or below the range of no-observed-adverse-effect level (NOAELs) for oral DEHP exposure established by US and European agencies 4 , 40 and is estimated to result in an amniotic fluid concentration within the ranges observed in human amniotic fluid. 6 …”
Section: Methodsmentioning
confidence: 99%
“…38,39 The 5 mg/kg-day dose used in this study falls within or below the range of noobserved-adverse-effect level (NOAELs) for oral DEHP exposure established by US and European agencies 4,40 and is estimated to result in an amniotic fluid concentration within the ranges observed in human amniotic fluid. 6 After weaning at postnatal day 21, pups were weighed, and all animals received DEHP-free 7% corn oil control chow for the remainder of the study (Figure 1). Approximately 1 to 2 male and 1 to 2 female offspring per litter were followed until 5 months of age (n = 6 control animals per sex, n = 7 DEHP males, n = 5 DEHP females).…”
Section: Animal Exposure Paradigmmentioning
confidence: 99%
See 2 more Smart Citations
“…Another group of obesogens are phthalates, which are diesters of phthalic acid used to impart flexibility to plastic products and as carriers for fragrances in cosmetics. They can easily leach from these products and can be found in indoor air and house dust [21].…”
Section: Sources and Classes Of Obesogensmentioning
confidence: 99%